Pengembangan Media Pembelajaran Seni Budaya Materi Seni Rupa Kelas X Berbasis Flipbook di SMA Adabiah 1 Padang - Wahyu Darpindo; Yahya Yahya (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
The purpose of this research is to create fine art learning materials for Adabiah 1 Padang High School's grade X pupils using Flipbooks. The background of this study is the lack of enthusiasm among students to learn fine arts using traditional package books, which are generally seen as dull. The steps of analysis, design, development, implementation, and evaluation are all included in the 4-D model, which is the research approach utilized in development (Research and Development). The outcomes demonstrated how well Flipbook-based learning resources increased students' motivation to learn and helped them comprehend the ideas behind two- and three-dimensional fine arts. The implication of this research shows that Flipbook can be an alternative learning media that is interesting and effective, as well as relevant to learning needs in the digital era. The conclusion of this study is that Flipbook has high validity and practicality as a learning media, which can be implemented in fine arts learning in schools.